Even Wonder Woman Couldn’t Do It All: The Impacts of Superwoman Syndrome on Women with Incarcerated Partners - Gregorash , Alexis; Tadros , Eman; Jhuremalani , Anha (Applied Family Therapy Journal (AFTJ), 2023)
Incarceration affects approximately 2 million individuals, with about half the male population reporting they are in an intimate relationship; causing non-incarcerated partners to experience various stressors and challenges. Specific to women, there is a phenomenon called “Superwoman Syndrome,” which refers to various the roles women take on such as caregiver, partner, career woman, and breadwinner. This may lead to higher rates of stress and dissatisfaction, decreased family functioning, and dysfunctional patterns. This can also exacerbate feelings of resentment, dissatisfaction, and inundation, proliferating into negative feelings towards the family unit. Partner incarceration can exasperate these impacts, leading to higher rates of stress and other mental health concerns. Our goal is to address the lacunae in literature regarding the social, emotional, financial, and systemic needs of females with incarcerated partners, through advocacy of policy changes. Further, empirical exploration and research into this population can help to mitigate some of the negative effects, and produce better outcomes for both individual women, and their families.